Synthesis, spectral characterization and antibacterial studies of palladium(II) complexes of heterocyclic thiones. Issue 5 (2009) - Tirmizi Tirmizi, Syed Ahmed Syed Ahmed; Nadeem Nadeem, Shafqat Shafqat; Hameed Hameed, Abdul Abdul; Wattoo Wattoo, Muhammad Hamid Sarwar Muhammad Hamid Sarwar; Anwar Anwar, Aneela Aneela; Ansari Ansari, Zameer Ahmed Zameer Ahmed; Ahmad Ahmad, Saeed Saeed
Abstract : Reactions of K2 [PdCl4 ] with heterocyclic thiones in molar ratios of 1:2 and 1:4 in water-methanol medium yielded the palladium(II) complexes with the general formula of either [Pd(L)Cl2 ], [Pd(L)2 ]Cl2 or [Pd(L)4 ]Cl2 where L ═ Imidazolidine-2-thione (Imt), 2-Mercaptopyridine (Mpy), 2-Mercaptopyrimidine (Mpm), 6-Mercaptopurine (6-Mp) and Thionicotinamide (Tna). The complexes were characterized by elemental analysis and spectroscopic (IR, 1 H and 13 C NMR) methods. An upfield shift in the >C═S resonance of thiones in 13 C NMR and downfield shift in N–H or aromatic proton resonances in 1 H NMR are consistent with the sulfur coordination to palladium(II). The complexes were screened for antibacterial activity, and the results showed that the complexes exhibited moderate activities as compared to that of a standard drug.